Sudan Infrastructure : A Continental Perspective - Ranganathan, Rupa; Briceno-Garmendia, Cecilia (World Bank, Washington, DC, 2017)
Improvements in infrastructure in all parts of Sudan in recent years have had a strong impact on per capita growth, contributing 1.7 percentage points. Consistent with trends in other countries, the information and communication (ICT) revolution that swept Africa contributed the most to Sudan. Raising the infrastructure endowment of all parts of Sudan to that of the region's best performer, Mauritius, could boosts annual growth by about 3.5 percentage points. Sudan has invested heavily in infrastructure in recent years, with some notable achievements. Power generation capacity tripled in just a few years, rising from around 800 megawatts (MW) in 2005 to 2,687MW in 2007, with a shift toward hydropower. Nevertheless, service reliability remains an issue. In ICT, Sudan has made enormous strides in liberalizing the sector and as a result has attracted significant private capital. Mobile penetration soared from less than 1 percent in 2000 to 33 percent in 2009. Recent connectivity to an undersea fiber-optic cable has led to expansions in access, improvements in quality, and reduction in prices. Looking ahead, Sudan's most pressing infrastructure challenges lie in the water and transport sectors. Sudan's infrastructure development has so far had a national focus, and there is much that remains to be done to achieve greater regional integration. While internal road corridors are developed, connectivity with neighbors is largely absent. Sudan has a natural gateway to the sea through Port Sudan but the port's performance is severely hindered by long dwell times, high costs, and capacity constraints. Looking further ahead, Sudan has the potential to be a major hydropower exporter if additional capacity could be developed and transmission links with neighboring Nile Basin countries strengthened.